2021
DOI: 10.5014/ajot.2021.75s2-po93
|View full text |Cite
|
Sign up to set email alerts
|

Equine-Assisted Activities and Therapies for Adolescents with Autism Spectrum Disorder: The Lived Experience

Abstract: Date Presented 04/13/21 The purpose of this phenomenological study was to highlight the lived experience of adolescents with autism spectrum disorder who participated in equine-assisted activities and therapies (EAA/T) using semistructured interviews and thematic analysis. Research questions explored the client's perception of skills learned and whether clients recognized the generalization of skills. Implications for OT and conceptualizing the links between OT and EAA/T will be presented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…A review of music therapies for children with ASD acknowledged a lack of sufficient evidence in this population, but described how musicbased interventions that provide patients an opportunity to actively engage (i.e., singing, music-making, and synchronized rhythmic actions) demonstrate the most potential for benefit [59]. Similarly, in a systematic review, movement-based interventions were shown to have potential for benefit to body structure and function in autistic patients, but results were mostly not significant [35].…”
Section: Therapy Interventionsmentioning
confidence: 99%
“…A review of music therapies for children with ASD acknowledged a lack of sufficient evidence in this population, but described how musicbased interventions that provide patients an opportunity to actively engage (i.e., singing, music-making, and synchronized rhythmic actions) demonstrate the most potential for benefit [59]. Similarly, in a systematic review, movement-based interventions were shown to have potential for benefit to body structure and function in autistic patients, but results were mostly not significant [35].…”
Section: Therapy Interventionsmentioning
confidence: 99%